2019
DOI: 10.3389/fphar.2019.01466
|View full text |Cite
|
Sign up to set email alerts
|

The Comparative Study of the Therapeutic Effects and Mechanism of Baicalin, Baicalein, and Their Combination on Ulcerative Colitis Rat

Abstract: Introduction: Ulcerative colitis (UC) is an inflammatory bowel disease with a high incidence rate and a difficult treatment regimen. Recently, significant advances in the treatment of intestinal diseases, particularly UC, have been made with the use of the drugs baicalin and baicalein, separately or in combination. However, the therapeutic efficacy and mechanism of action of baicalin, baicalein, and their combination therapy, in the treatment of UC has not been fully elucidated.Materials and Methods: we constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 34 publications
1
39
0
Order By: Relevance
“…The roots of Scutellaria baicalensis have long been used in traditional Chinese medicine for the prophylaxis and treatment of numerous viral infections [ 116 , 117 , 118 ]. Two research groups evaluated the antiviral activity of S. baicalensis extracts and the main active ingredients, baicalin ( 26 ) and baicalein ( 27 ) ( Figure 23 ), against Vero E6 cells infected with SARS-CoV-2 [ 119 , 120 ].…”
Section: Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 99%
“…The roots of Scutellaria baicalensis have long been used in traditional Chinese medicine for the prophylaxis and treatment of numerous viral infections [ 116 , 117 , 118 ]. Two research groups evaluated the antiviral activity of S. baicalensis extracts and the main active ingredients, baicalin ( 26 ) and baicalein ( 27 ) ( Figure 23 ), against Vero E6 cells infected with SARS-CoV-2 [ 119 , 120 ].…”
Section: Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 99%
“…Several herbal medicines and natural products have shown antiviral activities against viral pathogens (8)(9)(10)(11). Among these, the roots of Scutellaria baicalensis Georgi (Huangqin in Chinese) are frequently used in TCM for the prophylaxis and treatment of hepatitis and respiratory disorders (12)(13)(14). In the present study, an enzymatic assay was performed to test if the ingredients isolated from S. baicalensis are inhibitors of SARS-CoV-2 3CLpro.…”
Section: Introductionmentioning
confidence: 98%
“…Baicalein (5,6,7-trihydroxyflavone), a flavonoid isolated from the roots of Scutellaria baicalensis and Scutellaria lateriflora is known to exhibit a wide range of biological properties [ 15 , 16 , 17 , 18 ]. Previous studies have demonstrated that baicalein, both in naked, as well as nanoparticle-encapsulated forms were biocompatible to human gingival epithelial cells [ 19 ].…”
Section: Introductionmentioning
confidence: 99%